Insulin-like Actions of Glucagon-like Peptide-1: A Dual Receptor Hypothesis - Tomas-Falco, Eva (2009)
GLP-1 (9-36)amide is the cleavage product of GLP-1(7-36) amide formed by the action of diaminopeptidyl peptidase-4 (Dpp4) and is the major circulating form in plasma. Whereas GLP-1(7-36)amide stimulates glucose-dependent insulin secretion, GLP-1(9-36)amide has only weak partial insulinotropic agonist activities on the GLP-1 receptor, but suppresses hepatic glucose production, exerts antioxidant cardioprotective actions, and reduces oxidative stress in vasculature tissues. These insulin-like activities suggest a role for GLP-1 (9-36)amide in the modulation of mitochondrial functions by mechanisms independent of the GLP-1 receptor. Here we discuss the current literature suggesting that GLP-1(9-36)amide is an active peptide with important insulin-like actions. These findings have implications in nutrient assimilation, energy homeostasis, obesity, and the use of Dpp4 inhibitors for the treatment of diabetes.